Fabrication of ciprofloxacin loaded alginate/cockle shell powder nanobiocomposite bone scaffold - Wong, Huai Li; Santhanam, Jacinta; Ng, Shiow Fern; Bharatham, B Hemabarathy (Life Sciences, Medicine and Biomedicine, 2023)
Orthopedic implant infection is one of the most challenging issues in bone tissue engineering industry. Hence, local delivery of antibiotics incorporated into a fabricated bone scaffold possibly provides a more rapid bacteria inhibitory effect. In this study, pure ciprofloxacin loaded alginate/cockle shell powder nanobiocomposite bone scaffolds are fabricated with 5 wt% and 10 wt% ciprofloxacin respectively and tested for drug encapsulation, drug release and antibacterial properties towards common implant infecting bacterial strains (Staphylococcus aureus and Pseudomonas aeruginosa). Results from the studies showed a low drug encapsulation and drug release regardless of the concentration of drugs loaded with no significant differences noted (p<0.05). However, bacterial inhibition studies through direct contact and using eluted samples from drug release studies showed some inhibitory effects towards the growth of both bacterial strains tested. These findings were further justified with microscopy observations on biofilm and bacterial colony formation. Mineralization studies conducted additionally indicated that the scaffolds characteristics was not compromised due to drug loading. Although pure ciprofloxacin may not be the most suitable antibiotic to be incorporated into the nanobiocomposite bone scaffold, the study did provide some insight to the possible use of the scaffold for future drug delivery applications.